Superinduction of alpha 2u globulin by actinomycin D: evidence for drug-mediated increase in alpha 2u mRNA. - Chatterjee, B (1979)
Actinomycin D, an inhibitor of DNA-dependent RNA synthesis, increased the hepatic concentration of alpha 2u globulin, an androgen-inducible protein in the rat. Spayed female rats with a marginally induced state of alpha 2u synthesis showed an approximately 5-fold increase in hepatic alpha 2u globulin within 3-6 hr after treatment with actinomycin D. Initial treatment of these animals with 5 alpha-dihydrotestosterone, followed by actinomycin D, resulted within 2-3 hr in a more than 2-fold increase in hepatic alpha 2u globulin compared to animals treated with the androgen alone. In spite of inhibition of hepatic synthesis of poly(A)-containing RNA to less than 25% of control, superinduction with actinomycin D resulted in a parallel increase in the translatable mRNA for alpha 2u globulin. These results showing increase in both alpha 2u globulin and its translatable mRNA after superinduction with actinomycin D support the concept of post-transcriptional repression of alpha2u synthesis.